Disaster communication in managing vulnerabilities - Moorthy, Ravichandran; Benny, Guido; Darshan Singh, Sarjit Singh (Universiti Kebangsaan Malaysia Press, 2018)
The management of information among various stakeholders in natural and human induced disasters is fundamental to the mitigation and effective disaster-relieve operations. Disasters always happen abruptly, and often with different levels of severity, posing a major challenge for effective information exchanges and coordination. Extended droughts, trans-boundary haze, earthquakes, floods, hurricanes, tsunamis, landslides, volcanic activities and severe weathers have created havoc and displaced populations in many parts of this continent. These events have given rise to the realization that a more concerted disaster management strategy is needed to manage disasters more effectively. The paper attempts to uncover the emerging patterns in disaster communication. By drawing from experiences in disasters, especially in Asia, the paper firstly conceptualizes disaster, vulnerabilities and disaster communication, in the broader literature on disaster. Secondly, it examines how the emerging features, such as disaster communication and coordination mechanism, the role of social media and technology, reliability of communication systems, social capital and cultural knowledge can assist first responders, care givers and disaster related agencies in helping disaster victims more effectively.